PERILAKU PEMAIN DAN NIAT BELI UNTUK PEMBELIAN ITEM GAME PADA GAME GENSHIN IMPACT - Setiawan, Rizky Ilham; Bayu Dirgantara, I Made; Fu'adi, Dhena Kamalia (Diponegoro Journal of Management, 2023)
ABSTRACT Genshin Impact is a game that belongs to the Massively multiplayer online role playing game (MMORPG) genre, where this game has become an important component in electronic business. The total revenue generated from this game worldwide is around $114.8 billion in 2020 and in 2022 it will rise to $164.3 billion. Because income is quite high, it is very important to understand how players will provide value in playing Genshin Impact and what factors will influence the relationship between buying interest in Genshin Impact. This research was conducted using a questionnaire method using a purposive sampling technique on 100 people who are members of the Antar Gamer Discord server. Then the data analysis method used is Structural Equation Modeling (SEM) with an analysis tool in the form of Partial Least Squares (PLS). The purpose of this study is to examine the factors that influence players' purchase intentions towards the Genshin Impact game and to examine the effect of flow on Genshin Impact's purchase intention and to analyze the moderating role of buying pleasure on the relationship between flow and purchase intention in the Genshin Impact game. The results show that skill and telepresence playing the Genshin Impact game have a positive effect on flow. In addition, the flow of the Genshin Impact game also has a positive effect on purchase intention, where this relationship can also be mediated by Continuance intention.